Convening Technologies: Blockchain and the Music Industry - Baym, Nancy; Swartz, Lana; Alarcon, Andrea (International Journal of Communication, 2019)
This article traces the debates occurring in the music industry where blockchain technology surged as an ideal solution for long-standing disagreements over distribution, publishing, licensing, sales, streaming, and listening. The projections (in conferences, media, opinion pieces, and academic reports) started as techno-utopian, but over time the discourse shifted from “radical” to “incorporative” goals. The technological dreams were scaled back as the scope of social challenges to technological solutions became clearer. Borrowing from Clive Barnett’s theory of convening publics, we argue that the role of the blockchain in this environment was not necessarily as a technological solution, but rather as a “convening” force that brought disparate actors together. Nonetheless, we still have to ask, who is invited to convene, and who is left out?